(untitled) (Revista Contexto & Saúde, 2025)
This research aimed to analyze the recorded cases of child violence in a state in the Legal Amazon during the COVID-19 pandemic. To this end, a document-based time series was carried out based on notifications of child abuse in the state of Tocantins from 2020 to 2021. The variables used were the year of aggression, sex and age of the victim and aggressor, place of occurrence, and type(s) of violence perpetrated. Simple descriptive statistics (absolute and relative frequency), measures of central tendency (mean and standard deviation), and the Chi-square test were used for categorical variables (outcome variable type of violence). A significance level of 5% (p≤0.05) was adopted. A total of 2,389 (100%) records were considered valid for analysis. In 2021, there were more records of child abuse than in 2020, going from 1,099 (46.0%) notifications in 2020, the start of the pandemic scenario, to 1,290 (54.0%) in the following year. In addition, in 2021, children had a 0.70 higher risk of suffering neglect and 0.82 psychological violence compared to 2020. It is concluded that child maltreatment was associated with the period, with a higher occurrence in the second year of the pandemic, the sex of the child and the aggressor, and the type of violence. These aspects signal the urgent need for intersectoral actions aimed at a culture of peace and gender equality, especially during the pandemic period.